Assessing Strategies For Improving The Social Security Of Construction Workers In Zimbabwe - Moyo, T.; Crafford, G.J.; Emuze, F. (Journal of Construction, 2019)
PURPOSE OF RESEARCH: The aim of this research is to propose corporate social responsibility strategies that can improve social security of construction workers in Zimbabwe. METHOD: A questionnaire survey obtained perceptions from site/ project managers and skilled and semi-skilled workers from construction companies and thirteen building projects, respectively, in Harare, Bulawayo and Shurugwi. FINDINGS: Site and project managers prioritised training workers on effects and the need for minimisation of consumption of natural resources within the communities while the workers considered outplacement services, retraining and severance benefits as most essential to them. RESEARCH LIMITATIONS: Responses were generated from site/project managers who may not be owners of construction companies, but have considerable influence on ways to improve the productivity and welfare of workers. PRACTICAL IMPLICATIONS: The study encourages inclusive and well-resourced social responsibility programmes for construction workers. ORIGINALITY/VALUE: The corporate social responsibility strategies identified will positively enhance the welfare of workers.
Published Article
Keywords: Construction; Social Security; Sustainability; Workers; Zimbabwe